The Effect of Travel Experience, Destination Image, and Destination Trust on Revisit Intention at Ubud Monkey Forest - Natasha Valentine Trius; Ni Ketut Wiwiek Agustina; Putu Gde Arie Yudhistira (International Journal of Social Science and Business, 2023)
Destination images from traveler ratings may rank differently from person to person. That is why a destination must maintain its image. The aim of this study is to investigate the influence of travel experience, destination image, and destination trust on the intention to revisit Monkey Forest Ubud in Bali, Indonesia. The subject of the research is tourists who have visited Ubud Monkey Forest, Bali. The type of research used is quantitative associative research. Simple random sampling was used a as sampling technique where as many as 400 respondents were selected with the Taro Yamane formula. Data collection using a questionnaire was tested and analyzed by SmartPLS 3 with a measurement model test (outer model), and a structural model test (inner model). This research combines the three constructs to determine their effect on revisit intentions and adds control variables, namely age, and gender. The results of this research indicate that the travel experience has a significant and positive effect on revisit intention, destination image has a significant and positive effect on revisit intention, and destination trust has a significant and positive effect on revisit intention. This research examines the revisit intention of domestic tourists only, further research can develop the research by examining both domestic and international tourists.